The antecedents of Indonesian Soloraya Students Choosing Private Universities - Arif Julianto Sri Nugroho; Haris Abdul; Setyawanti Dandang; Tasari Tasari; FS Anna; Nugroho Jati Agung; Marjukah Anis (Cita Konsultindo Research Center, 2023)
This study aimed at examining the factors that influence students' decisions to choose private universities in the Soloraya region including image dimensions and accreditation status, costs and scholarships, human resource factor, physical evidence, motivation and group factors. The novelty of the research modifies the model on medium-sized private universities in Soloraya. The research population is all students at five private universities in the Soloraya region. Respondent objects as a sample consists of 120 students in the early and middle semesters of study. The research method was carried out using a survey through a quantitative approach to collect data from respondents through a closed questionnaire. The sampling technique used is non-probability sampling with accidental sampling type. Quantitative test used factor analysis. The test results provide the results of the dimensions of image and accreditation status, costs and scholarships, human resource factor, physical evidence, motivation and groups have a role in motivating students to choose study programs at private universities. Dimension tests of factor analysis in the form of image factors and accreditation status, fees and scholarships are the dominant factors as variables because they have initial eigenvalues ​​and extraction sums of squared loading greater than the other dimensions